Temptations of Power: Islamists & Illiberal Democracy in a New Middle East. By Shadi Hamid. New York, Oxford: Oxford University Press, 2014, pp. 280. ISBN 978-0-19931405-8 - Abdel Salam, El Fatih Abdullahi (IIUM Press, 2017)
In 1989, Francis Fukuyama famously announced the “end of history.” The Berlin Wall had fallen; liberal democracy had won. But what of ‘illiberal’ democracy – the idea that popular majorities, working through the democratic process, might reject gender equality, religious freedom, and other norms that Western democracies take for granted? Nowhere has such considerations become more relevant than in the Middle East, where the uprisings of 2011 swept the Muslim Brotherhood and other Islamist groups to power. ...